2011
DOI: 10.1155/2011/786759
|View full text |Cite|
|
Sign up to set email alerts
|

(Photo)electrochemical Methods for the Determination of the Band Edge Positions of TiO2‐Based Nanomaterials

Abstract: TiO 2 -based nanomaterials play currently a major role in the development of novel photochemical systems and devices. One of the key parameters determining the photoactivity of TiO 2 -based materials is the position of the band edges. Although its knowledge is an important prerequisite for understanding and optimizing the performance of photochemical systems, it has been often rather neglected in recent research, particularly in the field of heterogeneous photocatalysis. This paper provides a concise account o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
183
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 331 publications
(208 citation statements)
references
References 219 publications
(218 reference statements)
4
183
0
1
Order By: Relevance
“…To modify the surface of TiO 2 with polyheptazine, the electrodes were placed in a Schlenk tube connected via an adapter with a flask containing 1 g of urea and heated in a muffle oven at 425°C for 30 min. 15 N-labeled urea (98%, Euriso-Top) has been used in the synthesis of samples for solid-state NMR.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To modify the surface of TiO 2 with polyheptazine, the electrodes were placed in a Schlenk tube connected via an adapter with a flask containing 1 g of urea and heated in a muffle oven at 425°C for 30 min. 15 N-labeled urea (98%, Euriso-Top) has been used in the synthesis of samples for solid-state NMR.…”
Section: Methodsmentioning
confidence: 99%
“…One possible strategy to overcome this problem is the use of alternative photochemical architectures in which the light-harvesting absorber (for example a dye) is able to inject electrons into a nanocrystalline layer of a wide-bandgap oxide with a relatively negative potential of the conduction band edge (e.g. for anatase TiO 2 at −0.15 V versus RHE [14,15]). At the same time, the light absorber must be coupled to an oxygen evolution cocatalyst (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…E FB is the potential at which the energy barrier of the depletion layer disappears, and if we neglect experimental perturbations (like potential drop across the Helmholtz-layer and specifically adsorbed ions), it corresponds to the electron Fermi level with respect to vacuum, ÀE F [6]. The E FB is usually obtained from Mott-Schottky plots from electrochemical impedance spectroscopy, as well as by some other electrochemical and spectro-electrochemical techniques [7][8][9]. The spectro/photo/ electrochemical measurements by Jankulovska et al [8] confirmed the positive offset of 0.2 eV between the CBMs of anatase and rutile, and other measurements, like EPR [10], photoluminescence [11], photocatalytic Ag + reduction [12,13] and H 2 evolution [14] on mixed-phase particles, also reported the CBM of anatase being higher than that of rutile.…”
Section: Introductionmentioning
confidence: 99%
“…By accessing the Eg value and assuming that Efb and the conduction band (Ecb) practically merges at the Eonset[43], then we can schematize an energy diagram for the two phases and position the Ecb and valence band (Evb)…”
mentioning
confidence: 99%